New boroester compound derived from hydroxyaldehyde with some of its complexes and evaluation of biological and medical activities - K., Hawraa Abd Al- Jabbar; Khaleel, Asmaa Mohammed Noori (Iraqi Journal of Science, 2025)
The ligand 4-formyl-2-methoxyphenyl dihydrogen borate (L) was synthesized through a 1:1 molar reaction between vanillin and boric acid. Additionally, the synthesis of metal complexes of L with Co(II), Ni(II), and Cu(II) was also described. All the synthesized compounds were described using spectroscopic methods like that FT-IR, 1H NMR, UV-VIS. Also thermal analysis (TG),atomic absorption (AAS), elemental microanalysis (C.H.N), melting point (m.p.), magnetic susceptibility, molar conductivity and chloride measurements. The experiments determined that all the complexes were non-ionic compounds that did not dissociate into ions in solution. Additionally, the proposed molecular structures of these complexes were found to be octahedral in geometry. For C1 (Co), C2 (Ni), and C3 (Cu), the complexes’ magnetic moments were (3.54,2.73, and 2), indicating that each complex was paramagnetic. The synthesized compounds have good anti-microbial properties against Escherichia coli (G-), Staphylococcus aureus (G+), and Candida albicans. All synthesized compounds were evaluated as an anti-cancer agent against human thyroid cancer (FTCI33), the result showed that the copper complex was more effective compared to vanillin, ligand and its other complexes. The synthesized compounds were examined for anti-oxidant agents, the result showed that the ligand and nickel complex have more antioxidant activity than the other synthesized compounds.